Pengembangan Media Index Card Match (ICM) dalam Meningkatkan Motivasi Belajar Pada Mata Pelajaran Akidah Akhlak di MA Ma’arif Durensewu - Yuniar Wati, Silvia (Risâlah Jurnal Pendidikan dan Studi Islam, 2026)
The Index Card Match learning model is one of the very enjoyable learning models forstudents because the concept of this learning model is centered around learning while having fun. The aim of this research is to determine how the implementation of Index Card Match (matchingpairs) in learning activities in the subject of Akidah Akhlak involves students being more activecompared to their teachers in learning the lesson material and evaluating how well studentsunderstand the material. Teachers always encourage students to be active by providing additionalvalue. Teachers should use learning models that motivate students to learn in the learning process.